2016
DOI: 10.1002/ehf2.12098
|View full text |Cite
|
Sign up to set email alerts
|

The CHA2DS2‐VASc score as a predictor of high mortality in hospitalized heart failure patients

Abstract: AimsAtrial fibrillation (AF) is common in patients with heart failure (HF). CHA2DS2‐VASc score was originally employed as a risk assessment tool for stroke in patients with AF; however, it has recently been used to predict not only stroke but also various cardiovascular diseases beyond the original AF field. We aimed to verify the CHA2DS2‐VASc score as a risk assessment tool to predict mortality in patients with HF.Methods and ResultsConsecutive 1011 patients admitted for treatment of HF were divided into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…5 However, it has recently been used to predict prognosis and adverse clinical events in numerous cardiovascular diseases, including heart failure, stable CAD, and ACS, irrespective of the presence or absence of AF. [6][7][8][9][10][11] Recently, in a study by Ü nal et al, 12 a CHA2DS2-VASc score of >2 has been found to be an independent predictor for incidence of stent thrombosis. More recently, we have shown that CHA2DS2-VASc score independently predicts contrast-induced nephropathy in patients with ACS treated by PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 However, it has recently been used to predict prognosis and adverse clinical events in numerous cardiovascular diseases, including heart failure, stable CAD, and ACS, irrespective of the presence or absence of AF. [6][7][8][9][10][11] Recently, in a study by Ü nal et al, 12 a CHA2DS2-VASc score of >2 has been found to be an independent predictor for incidence of stent thrombosis. More recently, we have shown that CHA2DS2-VASc score independently predicts contrast-induced nephropathy in patients with ACS treated by PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have demonstrated an association of the CHA2DS2-VASc score with cardiovascular prognosis and adverse outcomes in different patient populations, including heart failure, stable coronary artery disease (CAD), and ACS beyond the original AF field. [6][7][8][9][10][11][12] The predictive value of CHA2DS2-VASc score on ISR still remains unclear, although all of the components of the CHA2DS2-VASc score are important risk factors for ISR. For this reason, the present study was designed to evaluate the predictive value of the preprocedural CHA2DS2-VASc score on the development of ISR in patients who undergoing revascularization with bare-metal stent (BMS) by reason of the both stable CAD and ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the CHA 2 DS 2 -VASc score, which has been recently used as a risk scoring system for AF and stroke, also predicts mortality and morbidity in other cardiac diseases [17,23]. It has been shown that the CHA 2 DS 2 -VASc score might be a predictor for hospital mortality in patients with HF independently of all other comorbid parameters [24]. It has also been showed that the CHA 2 DS 2 (congestive heart failure, hypertension, age ≥75, diabetes mellitus, previous stroke or transient ischemic attack or thromboembolism) score could predict cardiovascular events in coronary artery disease patients without AF [25].…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of studies that evaluated the prognostic significance of the CHA 2 DS 2 -VASc in patients with HF [10][11][12][13][14][15] with emphasis on stroke and mortality. The majority assessed mortality in hospitalized patients, [12][13][14][15] and only one study evaluated its impact on hospitalizations. 10 Analysis of patients enrolled in the warfarin vs. aspirin in reduced cardiac ejection fraction (WARCEF) trial found that The CHA 2 DS 2 -VASc score predicted adverse outcomes in patients with systolic HF in sinus rhythm.…”
Section: Introductionmentioning
confidence: 99%